Demography of Agriculture: Regional Analysis of Bulgarian Farmers - Daniel Petrov (Indonesian Journal of Social Economics and Agricultural Policy (IJSEAP), 2026)
This study explores the role of social innovation in addressing the demographic decline and institutional deficits in Bulgaria’s agricultural sector. Utilizing a mixed-methods approach, the research combines documentary analysis of six international and national strategic policy documents with an empirical survey conducted among 196 agricultural producers, stratified by region (NUTS 2) and economic size (FADN classification). Findings reveal a significant disconnect between policy discourse and practical outcomes. Only 19% of farmers are aware of social innovation, while 58% lack successors, and 42% consider exiting the sector within five years. Limited digital infrastructure and low institutional trust further impede innovation uptake. Despite policy emphasis on digitalization, inclusion, and territorial cohesion, most small and medium farms remain excluded from support mechanisms. Based on this, the study recommends the creation of regional innovation platforms, institutional support for intergenerational transfer, targeted digital training, and the deployment of “innovation brokers.” The research contributes to rural development discourse by offering empirical insights into farmers’ perspectives and advancing region-specific policy implications. Its findings hold relevance for countries across the EU periphery and the Global South facing similar rural transitions.